Comparison of Automation Deployment Implementation on Google Cloud Virtual Machine Using Deployment Manager and Terraform - Ardelia, Naila; Lindawati, Lindawati; Anugraha, Nurhajar (Jurnal Teknologi Informasi dan Pendidikan, 2024)
Software development has significantly transformed in recent years, with organizations increasingly turning to cloud computing infrastructure to speed up and ease the development and implementation processes. Up until now, there are few studies testing the efficiency and performance of deployment automation using Google Cloud Deployment Manager, which is essentially a built-in infrastructure deployment service provided by Google Cloud Platform. Most studies tend to prefer using open-source software such as Terraform, Ansible, and Kubernetes. This research aims to compare the implementation of deployment automation using Google Cloud Deployment Manager and Terraform. Three parameters are used to compare the results of automation deployment implementation: deployment efficiency, website performance, and cost efficiency. The test results indicate that Google Cloud Deployment Manager outperforms Terraform in all three test parameters. Specifically, Google Cloud Deployment Manager demonstrated superior deployment efficiency, enhanced website performance, and better cost efficiency. Thus, it is concluded that Google Cloud Deployment Manager is a more effective solution for deployment automation compared to Terraform.